A revision of the Hypodematium glabrum complex (Pteridophyta: Hypodematiaceae) with the description of four new species - Fan, Xue-Ping; Zhang, Liang; Gao, Xin-Fen; Zhang, Li-Bing (Phytotaxa, 2021)
A taxonomic study of the Hypodematium glabrum complex (Hypodematiaceae) is presented based on morphological evidence. Five species are recognized in this complex, four of which are described as new. The four new species are all from Yunnan, China and include H. brevipilosum sp. nov., H. parvisorum sp. nov, H. subglabrum sp. nov, and H. truncatum sp. nov. A key to the species and information on their distributions, habitats, and major distinguishing characters are provided.